Strategi Hastag” 2019 Ganti Presiden” Sudrajat-Ahmad Saikhu Dalam Pilkada Jawa Barat 2018 - Indiana Ngenget; Nazimin Saily (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2020)
This research analyzes the 2018 West Java Provincial Election, more specifically the case of the hashtag campaign strategy, “2019 to Replace the President”, on the increase in the votes for the Sudrajat-Ahmad Saikhu ticket. The research method is qualitative and the type of research is descriptive-analytic. Data are collected through in-depth interviews and library research. The research finds that the movement had the following impacts: First, it contributed to the voting preference of those who previously had voted for Prabowo Subianto in the 2014 general election. Second, the other candidate Deddy Mizwar’s supporters switched sides to the Sudrajat-Ahmad Saikhu ticket due to the still strong sentiments of the 212 movement for the urban Muslim population. Third, the increase in vote share for the Sudrajat-Ahmad Saikhu ticket was partly shared by the fact that the Regencies of Bogor, Bekasi, and Sukabumi, as well as the Cities of Depok and Bekasi were PKS and Gerindra strongholds